Air plasma assisted spray coating of Pebax-1657 thin-film composite membranes for post-combustion CO₂ capture - Jiang, Xu (2022)
With recent focus on achieving carbon neutrality to tackle global warming, there is an increasing need for advanced carbon capture technology to reduce carbon emission to the atmosphere. Membrane separation is one of such technologies that can remove carbon dioxide (CO2) in an energy-efficient and cost-effective way. In particular, the well-studied thin-film composite (TFC) membranes based on commercial polyethylene oxide (PEO)-containing materials have demonstrated strong promise for large-scale industrial post-combustion CO2 capture. However, to realize high-performance PEO-based TFC membranes, a key challenge lies in maximizing the reduction in the thickness of the selective layer without compromising membrane integrity, which to date has achieved little progress probably due to the failure in addressing the poor selective/gutter layer interfacial compatibility issue. Here, we adopted a facile spray coating method to design a TFC membrane comprising an ultrathin Pebax-1657 selective layer, a polydimethylsiloxane (PDMS) gutter layer, and a porous polysulfone (PSF) substrate. To increase surface hydrophilicity and wettability for enhancing interfacial compatibility between the selective and gutter layers, the surface of the PDMS gutter layer was activated for a few seconds by air plasma prior to Pebax-1657 spray coating. Coupled with well-controlled spray coating manipulation, a defect-free Pebax-1657 selective layer with an ultrathin thickness as low as 30 nm could be formed. Correspondingly, the optimized TFC membrane exhibited a highest CO2 permeance at 2022 GPU with a CO2/N2 selectivity of close to 30.0, far surpassing the threshold for commercially viable post-combustion CO2 capture (CO2 permeance ≥1000 GPU and CO2/N2 selectivity ≥20). More importantly, the use of spray coating endows the TFC design with great scalability potential, rendering our membranes, which are made solely from commercially available materials, highly relevant for industrial CO2 separation.